Comparison of the quality of sleep and intensity of headache between school-age children with migraine, tension headache and healthy children - Cheraghi, Fatemeh; Shamsaei, Farshid; Faiazi, Afshin; Molaaei Yeganeh, Fahimeh; Roshanaei, Godratolah (Iranian Journal of Child Neurology, 2018)
Objective Headache and sleep problems are commonly reported in children, and both can adversely impact the child’s life. This study aimed to compare the sleep quality and intensity of headache between school-age children with migraine and tension headache and healthy children. Materials and Methods In this cross-sectional study, sample was 198 children 6-12 years old in three groups. Migraine and tension headache groups from the outpatient clinic of Imam Khomeini of Hamadan and healthy group from elementary schools were randomly selected (66 children in each group) Data were collected using demographic questionnaire, Child Sleep Habits Questionnaire (CSHQ), Numeric Scale of Pain Intensity and Wong- Baker Faces Pain Rating Scale. The data were analyzed using SPSS 16 software by descriptive statistic and multivariate ANOVA, one way ANOVA, chi-square, kruskal-wallis and linear regression tests. Results The majority of subjects in migraine group (57.6%), tension headache (60.6%) and healthy children (45.5%) were female. Approximately, 45.5% of children with migraine and 37.9% of them with tension headache had experienced severe headache. Only a significant relationship was seen between mean scores of headache intensity and sleep quality in migraine group (p< 0.05). There was a significant difference in mean scores of sleep quality among three groups (P<0.001). Conclusion The children with migraine experienced more unsuitable sleep in duration of severe headache. Highlighting the co-morbidity between intensity of headache and sleep problem of children with migraine and tension headache is important to improve treatment strategies and to know the impact of headache on their normal life.